Regulation, agro-energy policy and market evolution for renewable fuels in Brazil - Rodríguez Morales, Jorge Ernesto (2015)
The costs of oil dependence, the environmental external costs of fossil fuels, or the promotion of agricultural development, has justified a number of measures of state intervention to expand the domestic market of biofuels, assuming that state intervention is necessary and sufficient condition for achieving this aim. After analyzing the political and economic elements in the Brazilian ethanol sector in historical perspective, in this article we argue that the expansion or contraction of the market should not be understood as an effect of a particular policies determined by the regulatory state. Regarding this, we argue the trends on the market development reflect the effects of aprevious underlying relationship, which is determined by the convergence or divergence over time of the opportunity costs of government and agribusiness. Our analysis shows that the effectiveness of a policy of energy diversification as the promotion of biofuels depends on the economic benefits and political rents generated by expanding the use of ethanol. These restrictions can be extrapolated as part of the cost-effectiveness analysis of public policies related to the sector in other countries.